Earth science [electronic resource] : a scientific history of the solid Earth - Allaby, Michael (Discovering the earth, 2009)
Discusses the natural history of Earth, covering geology, botany, zoology, ecology, volcanology, seismology, geomorphology, meteorology, climatology, oceanography, and other scientific disciplines, with an up-to-date version of the geologic time scale, photographs, and sidebars